Social Support and its Relationship to Professional Stability Among Educational Counselors - Al-Zaidi, Qais Rashid Khawaf (Al-Adab Journal, 2021)
The research aims to identify: The level of social support for educational counselors. The level of professional stability of the educational counselors. The correlation between social support and professional stability among educational counselors. The current research is determined by educational counselors, male and female, in three general directorates of education in Baghdad Governorate (Rusafa First, Rusafa Second, and Rusafa Three) for the academic year (2017 - 2018) and after applying the standards to the sample members and conducting the data unpacking and dealing with them statistically, the results showed as follows, that the individuals of a sample the research enjoys social attribution, and it also showed that the members of the research sample do not enjoy professional stability, and the results also showed that there is no correlative relationship between the social attribution and the professional stability of the sample. In conclusion, it was recommended that the education directorates should satisfy the work environment and the needs of the individuals working within the school and suggested conducting a study on the school principals for the same concepts.